Helder Pessoa Câmara : elementos de seu perfil intelectual a partir de suas bibliotecas - Pina Neta, Lucy da Silva (2013)
Câmara, Hélder, 1909-1999; dissertations; religion; church; religious superiors - books and reading; religious biography